Dormancy release and germination of Echinochloa crus-galli grains in relation to galactomannan-hydrolysing enzyme activity - Bing-yan SONG; Jin-xiao SHI; Song-quan SONG (Journal of Integrative Agriculture, 2015)
Echinochloa crus-galli, one of the world's most serious weeds, influences seriously the yield and quality of cereal crop plant. It is well known that E. crus-galli grain is dormant, but its dormant type, as well as its dormancy release and germination in relation to galactomannan-hydrolysing enzyme activity were poorly understood. The cooperation of endo-β-mannanase (EC 3.2.1.78), β-mannosidase (EC 3.2.1.25) and α-galactosidase (EC 3.2.1.22) can hydrolyze the cell walls rich in mannan-based polymers. In the present paper, the mature grains are used as experimental materials, we investigated the water uptake of grains, the effect of removing partial endosperm, after-ripening, stratification and phytohormone on grain germination, and the change in endo-β-mannanase, β-mannosidase and α-galactosidase activities of grains during after-ripening and germination. The results showed that the freshly-collected grains were water-permeable and had only phase I and II of water uptake, while the grains after-ripened for 150 d had an obvious phase III of water uptake. In alternating photoperiod, the germination of grains freshly-collected was zero at 10–35°C, and that of half grains was 11% at 20°C only. The grain germination was notably promoted by after-ripening and stratification, but not by gibberellic acid and 6-benzyladenine at 0.0001–1 mmol L−1. β-Mannosidase activity increased during 0 to 300 d of after-ripening and then decreased. The activity of endo-β-mannanase and α-galactosidase of grains decreased with after-ripening. During grain germination, endo-β-mannanase and β-mannosidase activities obviously increased, while α-galactosidase activity decreased. Our data showed that E. crus-galli grain was a deep physiological dormant, the dormancy release by after-ripening was related to an increasing β-mannosidase activity, and its germination was closely associated with an increasing endo-β-mannanase and β-mannosidase activity; which have provided new knowledge to decrease the harm of E. crus-galli on production of cereal crop plant.